DISKURSUS KEAGAMAAN DALAM RUANG MAYA (Analisis Semiotik terhadap Diskursus Keagamaan dalam Halaman Facebook âAqidah Ahlussunnah: Allah Ada Tanpa Tempatâ) - , Nita Hamida Noeris, Prof. Susetyawan ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The tittle of this study is âReligious Discourse in the Cyberspace (Semiotic Analysis of Religious Discourse in the Facebook page âAQIDAH AHLUSSUNNAH: ALLAH ADA TANPA TEMPATâ). The theme was chosen because of existence of virtual space has become an integral part of the culture of today's society. The existence of Facebook as a public space in the virtual society's culture which is quite phenomenal has made Facebook as an alternative medium to perform various religious discourse. One thing that became the fundamental question is how far Facebook able to play a role as a representative space for religious dialogue that is democratic and egalitarian to various different views or beliefs. The question is then attempted to answer by using the method of semiotic analysis as a way to understand and describe the social realities that exist in society. The rool of semiotic as a tool of analysis is important to breaking the meaning of the sign that emerged in texts contained in the virtual space, in this case that is Facebook as a medium for religious discourse. Therefore, the research objectives of this study is the status and notes on a Facebook page âAQIDAH AHLUSSUNNAH: ALLAH ADA TANPA TEMPATâ. The study was conducted in two stages, that is historical research through the study of literature and internet search to understand the context of the study subjects, and the next is the interpretation, a process of interpretation of signs. The data was collected in three ways, that is documentation, observation and interviews. Further analysis of semiotic made to read the signs on the status which is uploaded in the page by using the perspective of Barthesian, that is through two order of signification, denotation, connotation and myth. The results of this study indicate that Facebook was not sufficiently representative to have a dialogue or discourse of religion and tend to progressively sharpen sectarian conflict there. This relates to Facebook's cyberspace situations where the communication that goes up is a mediated communication, that is by using the computer as a medium. With such a form of communication, the opportunity for the occurrence of distorted communication that is becoming increasingly high. Therefore, when the conditions are so used to talking about religion and everything associated with it, the better the chance for conflict becomes increasingly sharp as the question of religion is a matter of faith that knows only right or wrong, black or white.